The RESPON PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) DENGAN PEMBERIAN BERBAGAI KONSENTRASI PGPR (Plant Growth Promoting Rhizobacteria) AKAR KAKAO - Triono Bambang Irawan; Liliek Dwi Soelaksini; Anni Nuraisyah (Universitas Islam Kadiri, 2022)
The aims of this study were: (i) to determine the response of cocoa seedling growth to cocoa root PGPR; (ii) determine the appropriate PGPR concentration of cocoa roots for the growth of cocoa seedlings. The research was carried out in June – December 2021, located in the Jember State Polytechnic nursery with an altitude of 89 m above sea level. The study used non-factorial RAK, namely: PO = PGPR concentration 0 ml/liter/5 polybags; P1 = PGPR concentration 50 ml/ liter / 5 polybags; P2= PGPR concentration 100 ml / liter / 5 polybags; P3 = PGPR concentration 150 ml / liter / 5 polybags and 6 replications. The results showed: (i) Cocoa seedling growth response by giving PGPR (Plant Growth Promoting Rhizobacteria) Cocoa Roots had a significant effect on plant height, number of leaves, stem diameter, wet weight and dry weight of roots, number of roots and root volume; (ii) Provision of optimal PGPR concentration of cocoa roots on root dry weight : 109 ml / l and root wet weight : 99 ml / l.